(untitled) (Journal of Social Sciences Review, 2022)
The current research study explores the suffering of double consciousness in the character of Parizaad in Pakistani Urdu drama serial, Parizaad. It is a story which unfolds Marxist, racist and sociological themes. However, the researcher has utilized a non-empirical Textual Analysis Method of research along with following the concept of double consciousness by Du Bois as a theoretical framework for analyzing the drama serial to explore the research objective. The framework argues that black people are behaved racially which causes inferiority complex, second-sight and twoness in them. Similarly, the analysis of the drama serial in this research study manifested that Pakistani brown people, following white legacy of racism, consider themselves superior to their fellow blackish people. Also, the power of money is dominant, and such socio-economic factors cause double consciousness in the character of blackish-skin Parizaad.